Winning ways Jeannie Szoradi at the Jackson International Ballet Competition - Szoradi, Jeannie (Dance Books Ltd., Alton,Hampshire (UK), 1998)
PALABRAS CLAVE: Jackson International Ballet Competition, UNESCO International Theater Institute (ITI).